Komunikasi KPU dalam Menekan Golput di Jember - Ferdian Ardani Putra; Ahmad Fauzi (Jurnal Al-Hikmah, 2020)
Indonesia is a country that applies a democratic political system. One of the means of the democratic political system in Indonesia is the General Election. The implementation of a democratic election should be carried out in accordance with the election principles abided by Indonesia, namely Luber-Jurdil (Direct, General, Free, Confidential, Honest, Fair). In order for the principle of Luber-Jurdil to be carried out, supervisions are requireds. Supervision is not only carried out by Panwaslu (General Election Supervisory Agency), the public also have to play a role in that supervision. The public can monitor, either directly or indirectly, the process of running a democracy / elections. The results of the current study show that there were several causes of abstention in the last 2018 elections, namely: 1) Internal factors which include technical factor and occupational factor, 2). External factors which include administrative factor, and political factor. There are also solutions to reduce the number of abstentions for the next election by easing the rules for voters to be able to vote, improving the data collection and voter registration system so that it has fresher outlook (requires adequate personnel and budget support), changing the right to vote into an obligation to vote. The electoral system must be very easy for voters to understand (for example, easy voting procedures, simple ballot paper design). For those solutions, it is necessary to involve strategic groups, such as first-time voters, religious people, women, people with disabilities and marginalized groups.